PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN MENGKONSUMSI PRODUK KESEHATAN HERBALIFE DI KOTA TERNATE - Renawaty Machmud; Ibnu Sina Hi Yusud (Jurnal Manajemen Sinergi, 2013)
this study aims to determine the “influence of Product Quality Satisfaction Against Consuming Herbalife Health Products In Ternate.” In the 63 respondents, the method of analysis used in The studies are simple line are regression analysis method. Based on statiscal tests showed that the quality of products haved-count equal to 1.053. this value issmaller than the value oft-table (1.053 1.999) this result shows that the variable quality of the product (X) does not have asignificant effect oncustomer satisfaction (Y). It can be seenthat the number of R squares quaredor (0.134) of  0.018. figures R Squaries also known as the coefficient of determination. The magnitude of coefficient of determination 0.018 or 1.8%. The figure of 1.8% means that the quality of Herbalife products may affect customer satisfaction, while the remaining 98.2% (100%-1.8%) affected by other factors such as price and others.